Effects of UVB radiation on net community production in the upper global ocean - Lara S. Garcia‐Corral; Johnna M. Holding; Paloma Carrillo‐de‐Albornoz; Alexandra Steckbauer; María Pérez‐Lorenzo; Nuria Navarro; Pablo Serret; Carlos M. Duarte; Susana Agusti (Global Ecology and Biogeography, 2017)
Aim Erosion of the stratospheric ozone layer together with oligotrophication of the subtropical ocean is leading to enhanced exposure to ultraviolet B (UVB) radiation in ocean surface waters. The impact of increased exposure to UVB on planktonic primary producers and heterotrophs is uncertain. Here we test the null hypothesis that net community production (NCP) of plankton communities in surface waters of the tropical and subtropical ocean is not affected by ambient UVB radiation and extend this test to the global ocean, including the polar oceans and the Mediterranean Sea using previous results. Location We conducted experiments with 131 surface communities sampled during a circumnavigation cruise along the tropical and subtropical ocean and combined these results with 89 previous reports encompassing the Atlantic, Pacific, Arctic and Southern Oceans and the Mediterranean Sea. Methods The use of quartz (transparent to UVB radiation) and borosilicate glass materials (opaque to most UVB) for incubations allowed us to compare NCP between communities where UVB is excluded and those receiving natural UVB radiation. Results We found that NCP varies when exposed to natural UVB radiation compared to those where UVB was removed. NCP of autotrophic communities tended to decrease under natural UVB radiation, whereas the NCP of heterotrophic communities tended to increase. However, these variations showed the opposite trend under higher levels of UVB radiation. Main conclusions Our results suggest that earlier estimates of NCP for surface communities, which were hitherto derived using materials blocking UVB radiation were biased, with the direction and magnitude of this bias depending on the metabolic status of the communities and the underwater penetration of UVB radiation.